2017
DOI: 10.1002/ente.201600805
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Early‐Stage CO2 utilization Technologies—Comparing Apples and Oranges?

Abstract: CO2 utilization involves many disciplines -fields as different as apples and oranges. Technology assessment is a common tool for evaluation. This article analyses its current state in CO2 utilization. First the steps of chemical product development are matched with Technology Readiness Levels for classification. Second, relevant literature is selected and assessment methods, and indicators are examined. The analysis shows that standardization in CO2 utilization technology assessment is low. Current research ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 56 publications
0
67
0
Order By: Relevance
“…Still only 2 of 14 investigated reports mention acceptance in their results (Schlesinger et al, 2014;Bründlinger et al, 2018). Moreover, Zimmermann confirmed that "social assessment shows low or no representation" in further techno economic assessments (Zimmermann and Schomäcker, 2017). Critical points for the acceptance of the society globally are health, safety, food, and environmental risks, more precisely defined in the sustainable development goals (United Nations, 2015b).…”
Section: Acceptancementioning
confidence: 95%
“…Still only 2 of 14 investigated reports mention acceptance in their results (Schlesinger et al, 2014;Bründlinger et al, 2018). Moreover, Zimmermann confirmed that "social assessment shows low or no representation" in further techno economic assessments (Zimmermann and Schomäcker, 2017). Critical points for the acceptance of the society globally are health, safety, food, and environmental risks, more precisely defined in the sustainable development goals (United Nations, 2015b).…”
Section: Acceptancementioning
confidence: 95%
“…Schmidt et al (2004) and Manhart and Grieβhammer (2006) also concluded that data availability was a significant barrier in applying SLCA, which partly relates to the data collection at the company level. Zimmermann and Schomäcker (2017), who performed a review study on SLCA for early-stage CO 2 utilization technologies, also concluded that there is a limited application of SLCA for such technologies because companies are not yet established or have recently been developed. The latter was the case for our analysis since the social data for such early-commercial stage technologies are mostly available for large-scale companies and mainly exist internally (site-specific or within a company at a corporate level).…”
Section: A Critical View On Social Performance Assessment At Company mentioning
confidence: 99%
“…Besides, company managers and innovative industry investors argue that, at the moment, the environmental and economic concerns are their first priorities and the social concerns in European countries are of less importance to be assessed for such lower TRL technologies. Nevertheless, Falcone et al (2019) and Zimmermann and Schomäcker (2017) highlighted the importance of social assessment at the early stage of technology developments. The advantage of such results is that companies can use them to compare their performance with that of their specific sector and/or region in which they are active.…”
Section: A Critical View On Social Performance Assessment At Company mentioning
confidence: 99%
“…Several products manufactured using CO 2 as a feedstock have been studied and produced. An overview of the set of compounds and their technological path can be found in international reports (Parsons Brinckerhoff, 2011; Bocin-dumitriu et al, 2013; CO 2 Sciences and The Global CO 2 Initiative, 2016; Zimmermann and Schomäcker, 2017;, which are used to assign TRL to the chemicals described in section 2.3.…”
Section: Technical Groupmentioning
confidence: 99%